Market fields structure & dynamics in industrial automation - André P. Slowak (Universität Hohenheim, Forschungszentrum Innovation und Dienstleistung (FZID), 2009)
There is a research tradition in the economics of standards which addresses standards wars, antitrust concerns or positive externalities from standards. Recent research has also dealt with the process characteristics of standardisation, de facto standard-setting consortia and intellectual property concerns in the technology specification or implementation phase. Nonetheless, there are no studies which analyse capabilities, comparative industry dynamics or incentive structures sufficiently in the context of standard-setting. In my study, I address the characteristics of collaborative research and standard-setting as a new mode of deploying assets beyond motivations well-known from R&D consortia or market alliances. On the basis of a case study of a leading user organisation in the market for industrial automation technology, but also a descriptive network analysis of cross-community affiliations, I demonstrate that there must be a paradoxical relationship between cooperation and competition. More precisely, I explain how there can be a dual relationship between value creation and value capture respecting exploration and exploitation. My case study emphasises the dynamics between knowledge stocks (knowledge alignment, narrowing and deepening) produced by collaborative standard setting and innovation; it also sheds light on an evolutional relationship between the exploration of assets and use cases and each firm's exploitation activities in the market. I derive standard-setting capabilities from an empirical analysis of membership structures, policies and incumbent firm characteristics in selected, but leading, user organisations. The results are as follows: the market for industrial automation technology is characterised by collaboration on standards, high technology influences of other industries and network effects on standards. Further, system integrators play a decisive role in value creation in the customer-specific business case. Standard-setting activities appear to be loosely coupled to the products offered on the market. Core leaders in world standards in industrial automation own a variety of assets and they are affiliated to many standard-setting communities rather than exclusively committed to a few standards. Furthermore, their R&D ratios outperform those of peripheral members and experience in standard-setting processes can be assumed. Standard-setting communities specify common core concepts as the basis for the development of each member's proprietary products, complementary technologies and industrial services. From a knowledge-based perspective, the targeted disclosure of certain knowledge can be used to achieve high innovation returns through systemic products which add proprietary features to open standards. Finally, the interplay between exploitation and exploration respecting the deployment of standard-setting capabilities linked to cooperative, pre-competitive processes leads to an evolution in common technology owned and exploited by the standard-setting community as a particular kind of innovation ecosystem.
urn:nbn:de:bsz:100-opus-3374
Keywords: D71; M21; L69; O32; 650; standard-setting; innovation; industry dynamics and context; industrial automation